2020
DOI: 10.1111/jphp.13175
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profile and protective effect of Ocimum basilicum aqueous extract in doxorubicin/irradiation-induced testicular injury

Abstract: Objectives Combined chemotherapy and radiotherapy usually associated with various comorbidities especially on rapidly proliferating cells as testis. This study aimed to characterize main constituents of Ocimum basilicum L. (OB) aqueous extract and examine its protective effect on doxorubicin/irradiation (DOXO/IR)‐induced testicular injury in rats. Methods Spectrophotometric analysis showed considerable amount of polyphenolic (146.31 µg/mg) and flavonoid contents (28.63 µg/mg); UPLC‐ESI‐MS/MS analysis revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…cASP-9/3 plays a critical role in apoptotic signaling in the mitochondria (47). The activation of cASP-9/3 mediates cell apoptosis in various cell types (48)(49)(50). In addition, 1,25-dihydroxyvitamin-d3 induces neutrophil apoptosis in periodontitis with type 2 diabetes mellitus patients via the p38/MAPK pathway (51).…”
Section: Discussionmentioning
confidence: 99%
“…cASP-9/3 plays a critical role in apoptotic signaling in the mitochondria (47). The activation of cASP-9/3 mediates cell apoptosis in various cell types (48)(49)(50). In addition, 1,25-dihydroxyvitamin-d3 induces neutrophil apoptosis in periodontitis with type 2 diabetes mellitus patients via the p38/MAPK pathway (51).…”
Section: Discussionmentioning
confidence: 99%
“…Less used, but also effective in the extraction of flavones, are solvents such as diethyl ether, which is useful to extract such flavones as nevadensin and salvigenin in O. basilicum [105]. Fewer studies were observed with other solvents such as hot water extract that showed similar results to hydromethanolic and hydroethanolic extractions in the same plant [106]. On the other hand, some studies further fractionated the extract to isolate the compounds, as seen in the infusion of O. campechianum [107] and the methanolic extract of O. gratissimum and O. sanctum [100,101].…”
Section: Extraction Methods Of Flavones From Lamiaceae Plants 41 Conventional Methodsmentioning
confidence: 99%
“…It was suggested that the damages observed in the histological examinations may be due to the direct or indirect effects of doxorubicin (Çeribaşı et al., 2012). Some researchers have reported that doxorubicin leads to inducing chromosomal aberrations in spermatogonial cells, inhibiting DNA synthesis by interacting with DNA backbone leading to inhibition of the progression of topoisomerase II enzyme, interfering with cell divisions, disturbing pathways involved in stress/cell death, led to germ cell loss, and ultimately resulting in testicular dysfunctions (Ahmed et al., 2019; Ibrahim et al., 2020). In addition, Boussada et al.…”
Section: Discussionmentioning
confidence: 99%